ROLE OF OXIDATIVE STRESS IN THE PROMOTING ACTIVITIES OF PCBS - Glauert, Howard P. (2008)
PCBs are organic pollutants that persist and bioaccumulate in the environment. These chemicals induce and promote liver tumors in rodents. Previous studies have shown that they increase oxidative stress in the liver, including lipid peroxidation, oxidative DNA damage, and NF-κB activation. The objective of these studies was to determine if the promoting activities of PCBs could be inhibited by dietary antioxidants (vitamin E, selenium, or phytochemicals) or by knocking out the p50 subunit of NF-κB. In the antioxidant studies, female rats were first injected with DEN (150 mg/kg) and then administered 4 biweekly i.p. injections (300 μmol/kg/injection) of PCB-77, PCB-153, or vehicle; the number and volume of placental glutathione S-transferase (PGST)-positive foci were then quantified. Vitamin E did not influence the promoting activities of PCBs. Increasing dietary selenium above the recommended intake increased the number of foci induced but decreased their volume. Most of the phytochemicals examined (N-acetyl cysteine, β-carotene, resveratrol, EGCG) had no significant effect on the promoting activity of PCB-77. Ellagic acid increased and lycopene decreased the number of foci; ellagic acid, CoQ(10), and curcumin decreased the volume of foci. In the NF-κB knockout study, male mice were first injected with DEN (90 mg/kg); controls not receiving DEN were also studied. Both p50 −/− and wild-type mice were then injected biweekly 20 times with PCB-153 (300 (μmol/kg). In DEN-treated and DEN + PCB-treated mice, the incidence of tumors was lower in the p50 −/− mice than in wild-type mice. In mice receiving PCB-153, the tumor incidence and tumor volume were higher. The volume of tumors that were positive for glutamine synthetase was increased in mice administered PCB-153. This study shows that the promotion of hepatocarcinogenesis by PCBs is largely unaffected by dietary antioxidants but is diminished when NF-κB activation is impaired by the absence of the p50 subunit.